The serum levels of FGF23, sclerostin, osteoprotegerin do not explain the inverse relationship between coronary calcifications and bone mineral density evaluated using computed tomography - Laurence Ferrières; Michel Laroche; Yannick Degboé; Acil Jaafar; Jean Ferrières (Frontiers in Cardiovascular Medicine)
BackgroundOsteoporotic patients are at a higher risk of stroke or myocardial infarction compared to non-osteoporotic patients, and conversely, individuals who have experienced a myocardial infarction or stroke are at increased risk for low bone mineral density (BMD) or osteoporotic fractures. Some studies suggest that the relationship between osteoporosis and vascular calcification may stem from the dysregulation of common factors that are implicated in both bone remodeling and the formation of calcified vascular plaques.ObjectivesOur primary endpoint was to evaluate the correlation between bone mineral density and calcification score. Our secondary endpoint was to analyse the association between potential shared serum biomarkers and the calcification score or bone status.MethodsWe conducted a retrospective study between May and October 2015 in 94 patients who had undergone a thoracic CT scan, to assess their coronary risk by calculating an Agatston score. The scans were re-analysed to obtain volumetric bone mineral densities (vBMD). We measured osteoprotegerin, FGF23 and sclerostin in frozen serums from these patients.ResultsPatients with a calcium score of 0 had a significantly higher vBMD than patients with a calcium score > 0 (187.7 vs. 162.1, p 0.03). This relationship persisted after adjusting for age, sex, BMI and sedentarity (p 0.036). There was no significant relationship between FGF23, osteoprotegerin, or sclerostin levels and the calcium score or vBMD.ConclusionLower vertebral thoracic bone mineral density is significantly associated with an increased risk of vascular calcification. However, this relationship is not explained by the serum levels of FGF23, sclerostin, or osteoprotegerin.